Homoeopathic treatment of HPV infections previously treated by other methods - Queralt Gimeno, Lluïsa (British Homeopathic Journal, 1996)
Fourteen patients with recurring HPV (human papillomavirus) infections in the form of genital and/or cervical condyloma diagnosed on examination, by cytology, PAP and biopsy, and in most cases associated with CIN (cervical intraepithelial neoplasia) were assessed. All had been previously treated with a variety of microsurgical procedures with the infection recurring. They attended the homoeopathic clinic for treatment.The aim of this paper is to collect the results obtained with this chronic disease and to carry out a survey of different strategies in the administration of homoeopathic treatment, according to the different conventional treatments used.